A PRUNED VGG16 WITH HYBRID PREPROCESSING AND DATA BALANCING FOR ROBUST AND INTERPRETABLE LUNG CANCER CLASSIFICATION - Salih, Marwa; Ahmed Shakir, Mohammed (Science Journal of University of Zakho, 2025)
Lung cancer is the most common and deadliest type of cancer globally, creating a critical need for diagnostic tools that are not only accurate but also practical for clinical integration. This study introduces a robust, computationally efficient, and interpretable deep learning framework using Computed Tomography (CT) images to address limitations in existing models, such as high computational costs, poor data quality, and a lack of transparency. Our approach utilizes a VGG16 architecture, streamlined through structured pruning, which reduced the parameter count from 138.3M to 26.6M without compromising performance. We developed a hybrid pipeline with dual filtering and adaptive CLAHE to enhance image quality, while data diversity and imbalance were mitigated using hybrid augmentation and SMOTE. The model was trained with a rigorous strategy, including four-fold cross-validation and dual-phase fine-tuning with a dynamic learning rate, ensuring stable convergence. On a primary single-source dataset, the model achieved a test accuracy of 0.9910 and a Matthews Correlation Coefficient (MCC) of 0.9845. To validate real-world applicability, the framework was tested on a large multi-source dataset, demonstrating strong generalization with a balanced accuracy of 0.9693 and an MCC of 0.9427. Model interpretability was confirmed using Grad-CAM visualizations to highlight clinically relevant regions. This framework provides a highly accurate, computationally efficient, and generalizable solution with significant potential for clinical deployment as a reliable diagnostic aid